2017
DOI: 10.18632/oncotarget.16315
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin as a potential modality for the chemoprevention of breast cancer: A dose-response meta-analysis of cohort studies from 857,831 participants

Abstract: BackgroundPrevious meta-analyses on the relationship between aspirin use and breast cancer risk have drawn inconsistent results. In addition, the threshold effect of different doses, frequencies and durations of aspirin use in preventing breast cancer have yet to be established.ResultsThe search yielded 13 prospective cohort studies (N=857,831 participants) that reported an average of 7.6 cases/1,000 person-years of breast cancer during a follow-up period of from 4.4 to 14 years. With a random effects model, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 36 publications
0
34
1
1
Order By: Relevance
“…Our result of overall aspirin use and breast cancer risk was different from the article reported previously, [ 9 ] which reported that a borderline significant inverse association (RR = 0.94, 95% CI: 0.87–1.01) was observed between overall aspirin use and breast cancer risk. The difference might be explained that previous study just summarized the results of cohort studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our result of overall aspirin use and breast cancer risk was different from the article reported previously, [ 9 ] which reported that a borderline significant inverse association (RR = 0.94, 95% CI: 0.87–1.01) was observed between overall aspirin use and breast cancer risk. The difference might be explained that previous study just summarized the results of cohort studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results were consistent with the previous study. Lu et al [ 9 ] confirmed that breast cancer risk decreased as aspirin intake frequency and a trend of decreasing risk for more years of aspirin intake increased. They also concluded that the optimal aspirin dose for preventing breast cancer may be in the scope of <325 mg per day, 2 to 7 times/wk, along with long-term medication (>5 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although mammary carcinogenesis is not linked to specific infection agents, studies have suggested that NSAIDs may prevent breast cancer . A recent review updates new evidence from epidemiologic and clinical studies that address the effects of aspirin in mammary tumorigenesis . A meta‐analysis of cohort studies including 857,831 participants confirms that aspirin reduces the risk of breast cancer in a dose‐dependent manner …”
Section: Epidemiological Evidence For the Prevention Of Cancer By Aspmentioning
confidence: 99%
“…Data supporting pro-tumorigenic roles for COX2 include robust preclinical studies identifying COX2 as an oncogene [5][6][7][8] ; the demonstration that NSAID-based COX2 blockade inhibits cancer progression in preclinical models 9,10 ; and epidemiologic studies showing that NSAID use correlates with reductions in colon and breast cancer risk [11][12][13][14][15][16] . However, prospective clinical trials utilizing aspirin or celecoxib therapy for the prevention, recurrence and treatment of colon [17][18][19][20] or breast cancer 14,15,[21][22][23] show variable results. Further, within the breast cancer field, disparate results of COX2 immunohistochemical (IHC) studies call into question the reliability of COX2 as a breast cancer biomarker or therapeutic target [24][25][26][27][28][29] .…”
Section: Introductionmentioning
confidence: 99%